Changes in infant head shape: Developmental trends during the first year of life and secular changes observed in recent years - Eujin Lee; Hama Watanabe; Ryoya Saji; Fumitaka Homae; Gentaro Taga (PLoS ONE, 2026)
The cephalic index (CI), defined as the percentage of head width to length, has been used in multiple studies. However, CI only provides 2D information, and comprehensive methods to assess the 3D cranial shape are yet to be established. Currently the typical pattern of changes in the head shape in healthy infants remains to be determined. There are only a few studies that followed the changes during the first year of life at frequent intervals or investigated differences between the subpopulations. In this retrospective cross-sectional study, we aimed to identify the morphological changes in the head that occur during the first year of life in healthy Japanese infants and capture differences in relation to background characteristics including age and birth year. We used 1,980 records of measurement data including over the head distances from the left tragion to the right tragion and from the glabella to the occipital protuberance, and head circumference. Complete data across three measurements were available for 909 records. From these measurements, head length, width, and height were estimated to determine CI, volume and a head roundness measure, Globularity Index (GI), by ellipsoid approximation. During the first year, the estimated marginal mean of CI reached the highest level 100.57 (95% CI [97.64, 103.50]) at 6 months (Cohen’s d : 0.88–1.07, p < 0.001), displaying front-to-back flattening before declining to 90.12 (95% CI [85.22, 95.02]) at 12 months following the effect of age, controlling for sex and birth year. We also observed secular changes during the period from 2010 to 2019, with recent birth years presenting more elongated head shape at 3 months of age. These indicated that distinct morphological changes in the head which may result from different growth rates in specific regions occur and secular changes can be observed during the early periods of infancy.